Performance Evaluation of the Small-Animal nanoScan PET/MRI System - Nagy, Kálmán; Tóth, Miklós; Major, Péter; Patay, Gergely; Egri, Győző; Häggkvist, Jenny; Varrone, Andrea; Farde, Lars; Halldin, Christer; Gulyás, Balázs (Journal of Nuclear Medicine, 2013)
nanoScan is a high-resolution integrated system for consecutive PET and MR imaging of small laboratory animals. We evaluated the performance of the system, using the NEMA NU 4-2008 protocol for the PET component and the NEMA MS 1-2007, MS 2-2008, and MS 3-2007 standards for the MR imaging component. The imaging system uses magnetically shielded position-sensitive photomultiplier tubes and a compact 1-T permanent-magnet MR imaging platform. Spatial resolution, sensitivity, counting rate capabilities, and image quality parameters were evaluated in accordance with the aforementioned NEMA standards. Further in vivo evaluation experiments complement the physical validation results. The spatial resolution of the PET system enabled the 0.8-mm rods of a Derenzo phantom to be resolved. With point source and 2-dimensional filtered backprojection reconstruction, the resolution varied from 1.50 to 2.01 mm in full width at half maximum in the radial direction and from 1.32 to 1.65 mm in the tangential direction within the radius of 25 mm. Peak absolute sensitivity was 8.41%. Scatter fraction was 17.3% and 34.0%, and maximum noise-equivalent counting rate was 406 and 119 kcps in the mouselike and ratlike phantom, respectively. The image quality test found a nonuniformity of 3.52% and a spillover ratio of 6.2% and 5.8% in water and air, respectively. In testing of the MR imaging component, artifact-free images with high signal-to-noise ratio were recorded. Geometric distortion was below 5%, and image uniformity was at least 94.5% and 96.6% for the 60- and 35-mm radiofrequency coils, respectively. The nanoScan integrated small-animal PET/MR imaging system has excellent spatial resolution and sensitivity. The performance characteristics of the PET and the MR imaging components are not compromised as a result of their integration onto a single platform. Because of its combination of features and performance parameters, the system provides crucial advantages for preclinical imaging studies over existing PET/CT systems, especially in neurologic and oncologic research.